2017
DOI: 10.1590/1806-9061-2016-0357
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis of Relative Expression of Apob, Adfp and Fatp1 with Lipid Metabolism in Daweishan Mini Chickens

Abstract: Quantitative RT-PCR was applied to measure the relative expression levels of the adipose differentiation-related protein (ADFP) gene, fatty acid transport protein 1 (FATP1) gene and apolipoprotein B (ApoB) gene in subcutaneous fat, abdominal fat, liver and muscle at five growth stages (28, 49, 70, 91 and 112 d) to determine the effect of the expression ofthese genes on fat deposition in Daweishan Mini chickens. The relative expression of ADFP gene mRNA in the abdominal fat andthe liver was significantly diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The results of the present study showed that the ADFP gene is expressed in the abdominal fat, subcutaneous fat, liver and pectoralis muscle of both PC and WBC, which is consistent with previous research (Decai et al, 2017;Brasaemle et al, 1997;Zhao et al, 2010). In addition, ADFP gene expression level peaked in PC on d 70 in the liver, subcutaneous fat and pectoralis muscle, whereas in WBC, the highest ADFP expression levels in abdominal fat, liver, and pectoralis muscle were determined on d 91, 112, and 28, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The results of the present study showed that the ADFP gene is expressed in the abdominal fat, subcutaneous fat, liver and pectoralis muscle of both PC and WBC, which is consistent with previous research (Decai et al, 2017;Brasaemle et al, 1997;Zhao et al, 2010). In addition, ADFP gene expression level peaked in PC on d 70 in the liver, subcutaneous fat and pectoralis muscle, whereas in WBC, the highest ADFP expression levels in abdominal fat, liver, and pectoralis muscle were determined on d 91, 112, and 28, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Although many research studies have been devoted to the regulation of the ADFP gene in mammals, to the best of our knowledge, no studies on the role of the ADFP gene in Yunnan Native chicken breeds have been published, except for the research of Decai et al (2017). The objective of the present study was to detect the tissue-specific expression of the ADFP gene in Piao chickens (PC) and Wuliangshan black-bone chickens (WBC) in order elucidate its role in fat deposition in two Yunnan native chicken breeds.…”
Section: Variations In Tissue-specific Expression Of Adipose Differenmentioning
confidence: 99%
See 3 more Smart Citations